(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study uses analytical methods to investigate the effect of evaluation and regulation on Indian consumption. The research looks at the regularity and dispositions of consumer activities. The impact that these intangibles have on the analytical and deliberative processes is also explored. The study also probes respondents to gauge their familiarity with and opinions on consumer protection and responsible consumption regulations (Sharma, 2020). The report also considers the impact of legislative constraints and recommendations on consumers’ purchasing habits. Finally, this study looks at how ethical and environmentally responsible business practices impact final judgments. The results shed light on India’s nuanced consumer behavior, highlighting the need of figuring out how to analyze and regulate consumption responsibly